DISABILITY AND SOCIAL MEDIA: EXPLORING UTILIZATION OF INSTRAGRAM PLATFORM AS A TOOL FOR DISABILITY ADVOCACY - Ani Cahyadi; Agus Setiawan (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
Social media such as Instagram has been a tool to facilitate subjective interests of its users, either individually or collectively. Furthermore, Instagram is an effective campaign and advocacy tool for issues like disability and inclusiveness. Therefore, this study aims to explore how this platform is used as an advocacy tool for the disabled and its relation with disability advocacy from the phenomenological approach. The respondents in this study were two actors with disabilities, while the informants were four individuals from the Banjarbilitas group that care about disabilities. Data analysis was carried out using the Social Model of Disability. The discoveries of this study lead to two main points. Firstly, Instagram as a new social media, has transformed into an important networking platform, which provides opportunities for the disabled to advocate and negotiate their existence and that of their groups in relation to equality in society. Secondly, it has provided them with basic access to job vacancies, freedom to express themselves, connect with other individuals and share information and most significantly the opportunity to facilitate both their personal and group interest in order to increase their prosperity and accessibility progressively and comprehensively.